Visualization of mercury(ii) accumulation in vivo using bioluminescence imaging with a highly selective probe. Issue 14 (21st March 2018) - Ke, Bowen; Chen, Hui; Ma, Lin; Zingales, Sarah; Gong, Deying; Hu, Die; Du, Lupei; Li, Minyong
Abstract : A reaction-based bioluminescent probe for detection of mercury(ii ) in vitro and accumulation in vivo . Abstract : Mercury is a highly toxic environmental pollutant that negatively affects human health. Thus, an in vivo method for noninvasive imaging of mercury(ii ) and visualization of its accumulation within living systems would be advantageous. Herein, we describe a reaction-based bioluminescent probe for detection of mercury(ii ) in vitro and accumulation in vivo . The application of this probe would help to shed light on the intricate contributions of mercury(ii ) to various physiological and pathological processes.